Pre-suasive and persuasive strategies in the tweets of the Saudi Ministry of Health during the 2020 coronavirus pandemic: A corpus linguistic exploration - Ibrahim, Wesam M. A.; Abaalalaa, Hessah S.; Hardie, Andrew (Frontiers in Communication, 2022)
In this study, we assess the applicability and usefulness of a particular theoretical framework for qualitative analysis of communicative strategies in discourses from beyond the English language. The theory in question is Cialdini's model of persuasion (and the related concept of pre-suasion). We present an operationalisation of this framework in terms of concrete linguistic features, which is implemented using the computer-assisted methods of corpus linguistics. As a case study, we explore a particular type of Arabic-language online public discourse surrounding an issue of pressing contemporary concern, namely the COVID-19 Pandemic. Specifically, we use a large collection of texts produced by the Ministry of Health of Saudi Arabia via the medium of the Ministry's official Twitter account. The tweets in question were produced in the context of a campaign to persuade the public to modify their behavior to comply with policies on protective measures. While the use of corpus-assisted linguistic approaches to examine public discourses around socially or culturally prominent issues is well-developed in the Anglosphere, it remains much more rarely utilized in the Arab World context, and especially in application to discourses in the Arabic language itself. In addition to the contribution arising from the improvements generated in our understanding of the particular issue at hand, this paper aims to contribute to the broader field of Arabic linguistics by modeling a suitable approach—albeit one whose use we show to be subject to some complicating factors—to address other questions in the study of persuasive language in Arabic.